Rhetoric and rationality: a deconstruction of managerial and nursing discourse in the new NHS - Traynor, Michael (1996)
In 1991, the United Kingdom (UK) government introduced reforms of the National Health Service (NHS), the most recent in a series of successive rationalisations aimed at increasing accountability and containing the service's costs. These rationalisations featured the strengthening of managerial control over the traditional professions, among them medicine and nursing, a system of contracting between purchasers and providers of healthcare and an unprecedented emphasis on the control and measurement of inputs particularly in terms of workers' activities.